Unnecessary suffering during the slaughter of cattle and pigs: mapping stun quality and associations to stun-to-stick intervals - Jerlström, Josefine; Berg, Charlotte; Wallenbeck, Anna (Frontiers in Animal Science, 2025)
Ensuring that animals remain unconscious and insensible until death occurs via blood loss is critical for animal welfare at slaughter. Two key factors are the rapid sticking procedure following stunning and a correct assessment of stunning efficiency. This observational study aimed to map and assess variations in stun quality among carbon dioxide (CO2) stunned pigs and mechanically stunned cattle slaughtered under commercial conditions in Sweden. It also examined whether the duration of the stun-to-stick interval was associated with signs of consciousness. Data were collected between May 2023 and November 2024 across five pig slaughterhouses (n = 2,795 pigs) and six cattle slaughterhouses (n = 330 cattle). Stun quality was assessed based on established protocols and categorised as either good, doubt, shallow or poor. The primary findings revealed that longer stun-to-stick intervals were significantly associated with inadequate stun quality (i.e. shallow or poor stunning) and significantly increased the likelihood of re-stunning. In total, 96.1% of the pigs were adequately stunned. Notably, the proportion of pigs with inadequate stun quality ranged from 1.2 to 16.6% across slaughterhouses, with poor stunning observed in 0 to 9.1%. Re-stunning rates varied from 1.6 to 6.4%, and stun-to-stick intervals ranged from 32 to 199 s. For cattle, 92.7% of the animals were adequately stunned, with inadequate stunning ranging from 0 to 18.5%, poor stunning from 0 to 14.8%, re-stunning rates from 0 to 14.0%, and intervals between 77 and 192 s. The results indicated that intervals of less than 59 s for pigs and 99 s for cattle were associated with the lowest rates of inadequate stunning. Furthermore, the observed variation in stun quality among slaughterhouses highlights the potential for improvement in stunning practices, particularly in slaughterhouses with higher rates of stunning failures. Not all animals displaying symptoms of inadequate stunning were identified by the slaughterhouse personnel; instead, they continued along the line, potentially conscious, which suggests critical gaps in monitoring. The correct use of stunning equipment, along with continuous training of personnel to accurately recognise signs of recovery, is crucial for protecting animals from unnecessary suffering throughout the slaughter process.